Diaphragm ultrasound evaluation during weaning from mechanical ventilation in COVID-19 patients: a pragmatic, cross-section, multicenter study - Luigi Vetrugno; Daniele Orso; Francesco Corradi; Gianluca Zani; Savino Spadaro; Francesco Meroi; Natascia D’Andrea; Tiziana Bove; Gianmaria Cammarota; Edoardo De Robertis; Samuele Ferrari; Marcello Guarnieri; et al. (Respiratory Research, 2022)
Abstract Background Diaphragmatic dysfunction is a major factor responsible for weaning failure in patients that underwent prolonged invasive mechanical ventilation for acute severe respiratory failure from COVID-19. This study hypothesizes that ultrasound measured diaphragmatic thickening fraction (DTF) could provide corroborating information for weaning COVID-19 patients from mechanical ventilation. Methods This was an observational, pragmatic, cross-section, multicenter study in 6 Italian intensive care units. DTF was assessed in COVID-19 patients undergoing weaning from mechanical ventilation from 1st March 2020 to 30th June 2021. Primary aim was to evaluate whether DTF is a predictive factor for weaning failure. Results Fifty-seven patients were enrolled, 25 patients failed spontaneous breathing trial (44%). Median length of invasive ventilation was 14 days (IQR 7–22). Median DTF within 24 h since the start of weaning was 28% (IQR 22–39%), RASS score (− 2 vs − 2; p = 0.031); Kelly-Matthay score (2 vs 1; p = 0.002); inspiratory oxygen fraction (0.45 vs 0.40; p = 0.033). PaO2/FiO2 ratio was lower (176 vs 241; p = 0.032) and length of intensive care stay was longer (27 vs 16.5 days; p = 0.025) in patients who failed weaning. The generalized linear regression model did not select any variables that could predict weaning failure. DTF was correlated with pH (RR 1.56 × 1027; p = 0.002); Kelly-Matthay score (RR 353; p < 0.001); RASS (RR 2.11; p = 0.003); PaO2/FiO2 ratio (RR 1.03; p = 0.05); SAPS2 (RR 0.71; p = 0.005); hospital and ICU length of stay (RR 1.22 and 0.79, respectively; p < 0.001 and p = 0.004). Conclusions DTF in COVID-19 patients was not predictive of weaning failure from mechanical ventilation, and larger studies are needed to evaluate it in clinical practice further. Registered: ClinicalTrial.gov (NCT05019313, 24 August 2021).